Scientometrics and evaluation of humanities and social sciences - Pečarić, Đilda (2013)
The more intense and stricter demands of scientific policy is that scientific production in the Humanities and Social Sciences be evaluated with bibliometrics methods and indicators (by impact factor, publishing in most cited journals, citations and visibility in „prestigious“ data bases, etc.). Theoreticians and advocates of bibliometrics and scientometrics methods are very skeptical regarding the application of these indicators in Humanities and Social Sciences. Social sciences and humanities do not have only scientific function. Papers are published on national languages and are not primarily intended for scientific communication but for much larger audience. That means that papers, essays and books in Humanities and Social Sciences have also cultural, educational, social and political purposes. In spite of actual philosophy of globalization and theory that science is (or must be) international - it is a fact that Humanities and Social Sciences are primarily oriented to the research and promotion of cultural and national identity. Their subjects bind them to the national domain, although this does not exclude a multinational research, international comparisons and exchange of experiences. Our stand is that papers in Humanities and Social Sciences cannot be measured by strict standards of scientific communication taken from the natural, medical and engineering sciences (in terms of communication forms). Because the data do suggest that this approach eliminates as non-scientific work 2/3 of production of workers in the Humanities and Social Sciences. It is obvious that cultural, educational, political and pedagogical functions are an integral part of the social and scientific responsibility of the author in the Humanities and Social Sciences. Therefore, their activity can be measured rather by influence factor and not by impact factor on which literal application of scientometric’s methods insists.
Zbornik indeksiran u sljedećim bazama: ISI (Thomson Reuters) ELSEVIER SCOPUS ACM - Association for Computing Machinery Zentralblatt MATH British Library EBSCO SWETS EMBASE CAS - American Chemical Society CiteSeerx Cabell Publishing Electronic Journals Library SAO/NASA Astrophysics Data System EI Compendex Engineering Village CSA Cambridge Scientific Abstracts DoPP GEOBASE Biobase American Mathematical Society (AMS) Inspec - The IET Ulrich's International Periodicals Directory
Projekt MZOS
ENG